Cerebral ischemia-reperfusion injury: mechanisms and promising therapies - Yang, Mingming; Liu, Boya; Chen, Bingqian; Shen, Yuntian; Liu, Guangliang (Frontiers in Pharmacology, 2025)
Cerebral ischemia-reperfusion injury (Cerebral I/R injury) is a critical pathological process following ischemic stroke, closely associated with multiple mechanisms including oxidative stress, neuroinflammation, and neuronal apoptosis. It also involves the alteration and regulation of numerous key genes and non-coding RNAs. Due to its complex regulatory mechanisms, there are currently no Food and Drug Administration (FDA)-approved drugs specifically targeting Cerebral I/R injury. Developing effective therapeutic strategies for Cerebral I/R injury remains a significant challenge in medical research. This review summarizes current treatment approaches for Cerebral I/R injury, which include traditional drugs, antioxidants, neuroprotective agents, exosomes, noncoding RNA therapeutics and combined intervention therapy. Pharmacotherapies exert positive effects on Cerebral I/R injury through antioxidative, anti-inflammatory, and neuroprotective mechanisms. Exosomes and noncoding RNA therapeutics can mitigate brain cell damage and promote neural function recovery by regulating the expression of downstream key genes via miRNAs, demonstrating potential as novel therapeutic options. Emerging evidence indicates that combined therapeutic strategies incorporating nanoparticle-mediated targeting demonstrate efficacy in treating cerebral I/R injury. By exploring the mechanisms of action and clinical application prospects of these different treatment strategies, this review aims to provide new insights and methods for the clinical management of Cerebral I/R injury.